Memoria colectiva y representaciones sociales de la historia en América, Europa y Palestina - Méndez Casas, Lander (2023)
This article reviews and synthesizes 10 free-recall studies on collective memory carried out in Latin America, Europe, and Palestine. Results show the high prevalence of the topics of politics, collective violence and warfare, but around 50% of recalled events were appraised as positives, disconfirming a negative bias in collective memory. However, in Palestine most of the events were entirely or partially negative, reflecting country’s conflictual situation. The analyzed studies confirm a partial socio-centrism: in Latin America and Palestine most events were national. A meta-analysis confirms a generational effect in 24/100 historical events. Negative historical events were related to low social wellbeing in Palestine. Results are discussed in the framework of collective memory processes and social representations of history.